An n‐n Heterojunction Configuration for Efficient Electron Transport in Organic Photovoltaic Devices. (21st December 2022) - Li, Yaohui; Wu, Xiang; Zuo, Guangzheng; Wang, Yufei; Liu, Xianjie; Ma, Yanxian; Li, Bolun; Zhu, Xu‐Hui; Wu, Hongbin; Qing, Jian; Hou, Lintao; Cai, Wanzhu
Abstract: Selective electron transport and extraction are essential to the operation of photovoltaic devices. Electron transport layer (ETL) is therefore critical to organic photovoltaics (OPV). Herein, an ETL configuration is presented comprising a solution‐processed n‐n organic heterojunction to enhance electron transport and hole blocking, and boost power conversion efficiency (PCE) in OPV. Specifically, the n‐n heterojunction is constructed by stacking a narrow‐band n ‐type conjugated polymer layer (PNDIT‐F3N) and a wide‐band n ‐type conjugated molecule layer (Phen‐NaDPO). Based on the ultraviolet photoelectron spectroscopy measurement and numerical simulation of current density‐voltage characteristics, the formation of the built‐in potential is investigated. In three OPVs with different active layers, substantial improvements are observed in performance following the introduction of this ETL configuration. The performance enhancement arises from the combination of selective carrier transport properties and reduced recombination. Another contributing factor is the good film‐forming quality of the new ETL configuration, where the surface energies of the related materials are well‐matched. The n‐n organic heterojunction represents a viable and promising ETL construction strategy for efficient OPV devices. Abstract : Selective charge‐carrier transport and extraction are essential in photovoltaic devices. Herein, a new electron transport layer configuration composed of two solution‐processed n ‐type materials (PNDIT‐F3N & Phen‐NaDPO) is constructed for organic photovoltaic devices. This "n‐n heterojunction" provides a built‐in potential that enables cascade electron transport energy level alignment and enlarges the hole‐blocking barrier, effectively boosting the power conversion efficiency.